A Carbazole-Based Aggregation-Induced Emission “Turn-On” Sensor for Mercury Ions in Aqueous Solution - Radha, Remya (2025)
The development of rapid detection methods to identify mercury ions in aqueous solutions is crucial for effectively monitoring environmental contamination. Fluorescent chemical sensors offer a fast and reliable approach to detect and analyze these metal ions. In this study, a sensor utilizing aggregation-induced emission (AIE) is introduced as a ’turn-on’ fluorescent sensor specifically designed for mercury ions in aqueous solutions. The sensor, based on carbazole, forms aggregates in aqueous solutions, resulting in a significant 800% enhancement of its fluorescence signal. When elemental iodine is added to the solution, the fluorescence of the aggregates is quenched by 90%. However, upon subsequent addition of mercury ions, the fluorescence is regenerated, and the intensity of the emission signal is directly proportional to the concentration of the ions across a wide concentration range. The carbazole-iodine complex acts as a fluorescent probe, enabling the detection of mercury ions in aqueous solutions.